2019
DOI: 10.1101/753624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serotonergic modulation of walking inDrosophila

Abstract: 16To navigate complex environments, animals must generate highly robust, yet flexible, locomotor 17 behaviors. For example, walking speed must be tailored to the needs of a particular 18 environment: Not only must animals choose the correct speed and gait, they must also rapidly 19 adapt to changing conditions, and respond to sudden and surprising new stimuli. 20Neuromodulators, particularly the small biogenic amine neurotransmitters, allow motor circuits 21 to rapidly alter their output by changing their func… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 106 publications
0
10
0
1
Order By: Relevance
“…Instead, 10Bα neurons drive pauses in walking behavior. Previous behavioral experiments found that flies will stop walking when they sense the ground vibrating (Fabre et al, 2012;Howard et al, 2019)-10Bα neurons may mediate this stopping via vibration-sensitive inputs from the FeCO. If true, this would imply that the FeCO functions as both a proprioceptive and exteroceptive organ.…”
Section: Behavioral Function Of Central Proprioceptive Neuronsmentioning
confidence: 98%
See 1 more Smart Citation
“…Instead, 10Bα neurons drive pauses in walking behavior. Previous behavioral experiments found that flies will stop walking when they sense the ground vibrating (Fabre et al, 2012;Howard et al, 2019)-10Bα neurons may mediate this stopping via vibration-sensitive inputs from the FeCO. If true, this would imply that the FeCO functions as both a proprioceptive and exteroceptive organ.…”
Section: Behavioral Function Of Central Proprioceptive Neuronsmentioning
confidence: 98%
“…Behavioral studies of walking flies demonstrate that vibration of the substrate can cause flies to stop walking (Fabre et al, 2012;Howard et al, 2019). To determine if 10Bα neurons could drive this pausing behavior, we optogenetically activated 10Bα neurons in tethered, intact flies walking on a spherical treadmill (Fig.…”
Section: Activation Of 9aα Neurons Causes Extension Of the Tibia-tarsmentioning
confidence: 99%
“…Most notable are the biogenic amines (e.g. Serotonin, a prominent bio-amine, was recently reported to inhibit walking behaviour in Drosophila ; Howard et al, 2019). Hence, it may well be that the (spatial and temporal) immediate social environment affects biogenic amine levels, and these in turn modulate the walking-related behavioural kinematics manifested in the different behavioural states.…”
Section: Discussionmentioning
confidence: 99%
“…The DVGlut-LexA 79 driver was derived from the pCaSpeR VGlut >> LexA construct 80 by removing the FRT cassette with KpnI restriction enzymes. Transgenic lines were generated by standard P-element-mediated transformation procedures in a yw background.…”
Section: Methodsmentioning
confidence: 99%